2015
DOI: 10.15713/ins.jcri.90
|View full text |Cite
|
Sign up to set email alerts
|

Phonophoresis in temporomandibular joint disorders: A clinical trial

Abstract: Background and Objective: Temporomandibular joint disorders (TMDs) are identified as a major cause of non-dental pain in the orofacial region. An effective drug delivery into this complex joint can result in a good prognosis. Phonophoresis is a novel phenomenon that exponentially increases the absorption of topical pharmacological compounds and achieves effective therapeutic drug concentration at the target site. Hence, this study is designed to assess the feasibility and effectiveness of aceclofenac gel phono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Deep heat (thermal US effect) causes local vasodilatation, which increases cell permeability and pain relief. Moreover, acoustic pressure waves (non-thermal US effect) causes the cells to oscillate at high speed (vibration) and to disrupt the membrane favoring the diffusion of the anti-inflammatory drug (diclofenac) (16). We postulate that the anti-inflammatory effect of diclofenac plus the biological effect of US (19) are capable of ameliorating TMD symptoms, a fact that has been demonstrated in this study.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Deep heat (thermal US effect) causes local vasodilatation, which increases cell permeability and pain relief. Moreover, acoustic pressure waves (non-thermal US effect) causes the cells to oscillate at high speed (vibration) and to disrupt the membrane favoring the diffusion of the anti-inflammatory drug (diclofenac) (16). We postulate that the anti-inflammatory effect of diclofenac plus the biological effect of US (19) are capable of ameliorating TMD symptoms, a fact that has been demonstrated in this study.…”
Section: Discussionsupporting
confidence: 57%
“…The only known study that evaluated phonophoresis with aceclofenac gel on TMD used a protocol similar to ours (1 MHz/0.8 -1.5 W/cm 2 /10 minutes). In that study, a frequency of 1 MHz showed higher transport than 3 MHz on topical gel application (16). In the referred study, their similar protocol decreased pain both in males (from 7 to 2.1 points) and females (from 7.85 to 3.6 points) and improved mouth opening both in males (from 33.5 ± 8.4 to 39.7 ± 7.8 mm) and in females (from 29.2 ± 7.3 to 34.3 ± 8.8 mm) (16).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…[27] When a medicine is administered using phonophoresis, it is transmitted to deep tissues using US energy, and the clinical outcome is related to the drug pharmacological activity. [26] Vijayalakshmi et al [28] used aceclofenac gel phonophoresis on TMD and concluded that it is effective and feasible in reducing symptoms of TMD.…”
Section: Discussionmentioning
confidence: 99%